Model Optimalisasi Pemberdayaan Ekonomi Masyarakat Berbasis Masjid: Studi Kasus Kota Depok - Kostaman, Koskos (Jurnal Ilmiah Ekonomi Islam, 2023)
Rasulullah SAW has given an example of the importance of empowering people after he migrated from Mecca to Medina. Among the aspects of empowerment that he did were spiritual, social, educational, and economic aspects. Empowerment of the poor is important in the social field. Poverty is a global issue that has an impact on development of a region. The government has been creating and developing programs to empower the poor for a long time, but it seems that it has not played on optimal role. Depok City BPS released that Depok City’s poverty rate in 2022 is 2.53%. and in 20202 the number of Muslims in Depok City is 1.773.341 out of a total population of 2.484.000. the means that more than 70% of Depok City’s population is Muslim. Muslims are synonymous with mosques, and Depok City has more than 400 mosques that can be empowered. Therefore, this study discusses the Optimization Model of Mosque-based Community Empowerment. The research methodology used is qualitative which camos from interviews and observations. Sources of data obtained directly from interviewees. The analysis technique used in this study is descriptive analysis by explaining the results of the researchers’ observations through a detailed explanation of the model. The result of this study are expected to be a source of reference for mosques in empowering communities.